Marginal no more: the equalization of campus and municipal police - Patten, Ryan (Journal of crime and justice, 2024)
Research of campus police has consistently demonstrated that they are viewed as less than or ‘not real cops,’ even though campus police possess full law enforcement powers. Using the liminality theoretical framework, this study examines four campus communities’ perceptions of campus and municipal police legitimacy. This study surveyed students, faculty, staff, and administrators using an online survey instrument across the participating campuses (N = 2,488). Even though the college campuses vary greatly regarding their population, settings, region, crime rates, and racial diversity, this study found remarkably consistent findings across campuses and classifications of respondents. Across almost all questions and campuses, respondents frequently evaluated campus police as legitimate as municipal police, which is a stark deviation from the extant research in this area. The only difference in evaluation between campus and municipal police was respondents were much less likely to think campus police should be armed (73%) compared to their municipal counterparts (90%). This research adds to the very small body of literature that finds campus police are finally being viewed as legitimate police.